Climate anomalies affect annual survival rates of swifts wintering in sub‐Saharan Africa. Issue 14 (6th July 2020) - Boano, Giovanni; Pellegrino, Irene; Ferri, Mauro; Cucco, Marco; Minelli, Fausto; Åkesson, Susanne
Abstract: Several species of migratory swifts breed in the Western Palearctic, but they differ in reproductive traits and nonbreeding areas explored in Africa. We examined survival and recapture probabilities of two species of swifts by capture–mark–recapture data collected in northern Italy (Pallid Swift Apus pallidus in Carmagnola, Turin, and Common Swift Apus apus in Guiglia, Modena) in the breeding season (May–July). Apparent survival rates were relatively high (>71%), comparable to other studies of European swifts, but showed marked annual variations. We used geolocators to establish the exact wintering areas of birds breeding in our study colonies. Common Swifts explored the Sahel zone during migration and spent the winter in SE Africa, while the Pallid Swifts remained in the Sahel zone for a longer time, shifting locations southeast down to Cameroun and Nigeria later in winter. These movements followed the seasonal rains from north to south (October to December). In both species, we found large yearly differences in survival probabilities related to different climatic indices. In the Pallid Swift, wintering in Western Africa, the Sahel rainfall index best explained survival, with driest seasons associated with reduced survival. In the Common Swift, wintering in SE Africa, the El Niño–Southern Oscillation (ENSO) cycle performed significantly better than Sahel rainfall or North Atlantic Oscillation (NAO). Extreme events and precipitation anomalies in Eastern Africa during La Niña events resulted in reduced survival probabilities in Common Swifts. Our study shows that the two species of swifts have similar average annual survival, but their survival varies between years and is strongly affected by different climatic drivers associated with their respective wintering areas. This finding could suggest important ecological diversification that should be taken into account when comparing survival and area use of similar species that migrate between temperate breeding areas and tropical wintering areas. Abstract : We examined survival and recapture probabilities of two species of swifts by capture–mark–recapture data collected in northern Italy in the breeding season, and we used geolocators to establish the exact wintering areas of birds breeding in our study colonies. Survival rates were relatively high (>71%) and showed marked annual variations related to different climatic indices. In the Pallid Swift, the Sahel rainfall index best explained survival, with driest seasons associated with reduced survival, while in the Common Swift the El Niño–Southern Oscillation (ENSO) cycle was associated with survival.